Ten-year trends in adverse drug reaction-related hospitalizations among people with dementia - Anum Saqib Zaidi; Gregory M. Peterson; Luke R.E. Bereznicki; Colin M. Curtain; Mohammed S. Salahudeen (SAGE Publishing, 2022)
Aim: Trends in the incidence of adverse drug reaction (ADR)-related hospitalizations have been studied in the general population, but not specifically in people with dementia. This study aimed to investigate trends in the incidence of ADR-related hospitalizations among people with dementia, and identify the most commonly implicated drugs and diagnoses in these admissions. Methods: This study utilized the administrative data of all adults admitted to the four major public hospitals of Tasmania, Australia, with a primary or secondary diagnosis of dementia from July 2010 to December 2019. ADR-related hospitalizations were identified by using diagnosis-based and external cause codes. The Cochran-Armitage test was used to examine trends in the incidence of ADR-related hospitalizations. Results: Of the 7552 people with dementia admitted to the hospital at least once within the study period, 1775 (23.5%) experienced at least one ADR-related hospitalization. The estimated annual incidence of ADR-related hospitalizations increased 18% (1484-1760 per 100,000 population with dementia, p for trend <0.05) from 2010 to 2019. For those ADR-related admissions with a drug code recorded, 19.3% were due to antithrombotics and 11.5% to antihypertensives. The most frequent ADR-related admission diagnoses were renal diseases (72.9%). Length of hospital stay and in-hospital mortality were both significantly greater for ADR-related, relative to non-ADR-related, admissions (median 7 versus 5 days and 11% versus 6.7%, respectively; p  < 0.001). Conclusion: The annual incidence of ADR-related hospitalizations in people with dementia increased between 2010 and 2019. Antithrombotics were the most commonly implicated drug class. The ADR-related hospitalizations were associated with increased length of stay and greater mortality. Plain Language Summary Adverse drug reaction-related hospitalizations among people with dementia Introduction: This study aimed to investigate trends in hospitalizations associated with medication problems among people with dementia, and identify the most commonly implicated drugs and diagnoses in these admissions. Methods: This study utilized the administrative data of all adults admitted to the four major public hospitals of Tasmania, Australia, with dementia from July 2010 to December 2019. Results: The annual incidence of hospitalizations associated with medication problems among people with dementia increased nearly 20% over 10 years. The length of hospital stay and in-hospital mortality were significantly greater for hospitalizations related to medication problems. Conclusion: The incidence of hospitalizations associated with medication problems in people with dementia increased between 2010 and 2019.